Penyuluhan Manajemen Pengelolaan Limbah Rumah Tangga Sebagai Upaya Pencegahan Stunting - Dimas Hanif Abdi Rahman; Andi Daramusseng; Chindy Sanjaya; Wulan Fitri Anjaswati (Abdimas Universal, 2022)
Indonesia is one of the countries with a fairly high number of stunting cases. One of the causes of stunting is poor environmental health conditions in the form of lack of access to clean water, inadequate sanitation, and poor waste management. Poor environmental sanitation factors increase infectious diseases such as diarrhea, Environmental Enteric Dysfunction (EED), and helminthiasis. These conditions can cause growth disorders to occur stunting and can increase mortality in toddlers. The purpose of this community service activity is to provide knowledge and understanding to the Gunung Kelua Village community about how to manage household waste (garbage and liquid waste) as an effort to prevent stunting. The method used is the lecture, discussion, and question and answer method. Based on the results of data analysis using the non-parametric test Wilcoxon result that there is a significant difference between before and after the extension activities of waste management (p-value 0.011 <0.05) and liquid waste management counseling (p-value 0.007 <0.05). Similar activities need to be carried out to support government programs in reducing stunting rates.